2012
DOI: 10.1063/1.4768842
|View full text |Cite
|
Sign up to set email alerts
|

Surface spin-glass, large surface anisotropy, and depression of magnetocaloric effect in La0.8Ca0.2MnO3 nanoparticles

Abstract: The surface magnetic behavior of La 0.8 Ca 0.2 MnO 3 nanoparticles was investigated. We observed irreversibility in high magnetic field. The surface spin-glass behavior as well as the high-field irreversibility is suppressed by increasing particle size while the freezing temperature T F does not change with particle size. The enhanced coercivity has been observed in the particles and we attributed it to the large surface anisotropy. We have disclosed a clear relationship between the particle size, the thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…8 For example, in materials such as manganites, the changes of magnetic and, in particular, magnetocaloric properties, have been investigated as a function of particle size, resulting, often, in a reduction of the MCE for smaller particles, where the reduction has been ascribed to the presence of a surface layer with properties different from the bulk. [9][10][11] On the other hand, a careful control of the thickness and the magnetic properties of this surface layer has been proposed in order to obtain a larger relative cooling power for nanoparticles when compared with the corresponding bulk material. 11 Within this scenario, it appears important a detailed characterization of the surface of magnetocaloric materials that, incidentally, is a largely unexplored research field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 For example, in materials such as manganites, the changes of magnetic and, in particular, magnetocaloric properties, have been investigated as a function of particle size, resulting, often, in a reduction of the MCE for smaller particles, where the reduction has been ascribed to the presence of a surface layer with properties different from the bulk. [9][10][11] On the other hand, a careful control of the thickness and the magnetic properties of this surface layer has been proposed in order to obtain a larger relative cooling power for nanoparticles when compared with the corresponding bulk material. 11 Within this scenario, it appears important a detailed characterization of the surface of magnetocaloric materials that, incidentally, is a largely unexplored research field.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] On the other hand, a careful control of the thickness and the magnetic properties of this surface layer has been proposed in order to obtain a larger relative cooling power for nanoparticles when compared with the corresponding bulk material. 11 Within this scenario, it appears important a detailed characterization of the surface of magnetocaloric materials that, incidentally, is a largely unexplored research field. This is partially due to the production methods typically employed for magnetocaloric systems that lead to a relatively weak control of the surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bi-magnetic nanocomposites and multilayers (and in particular hard-soft composites) have been shown to result in enhanced magnetocaloric effects [468][469][470][471]. Similarly, soft nanoparticles with a large surface anisotropy or spin-glass surface spins have also been proposed as candidates for strong magnetocaloric effects [472,473]. Although no magnetocaloric studies of hard-soft core/shell nanoparticles can be found in the literature, a recent report on Fe/-Fe 2 O 3 core/shell nanoparticles has revealed some interesting features (e.g., entropies changes of opposite sign at different temperatures), with contributions from both the core and the shell [474].…”
Section: Other Applicationsmentioning
confidence: 99%
“…Experimental data show that magnetic hysteresis is observed in LSMO NPs, unlike bulk samples where magnetic losses are not observed. According to Ref.…”
Section: Numerical Results and Discussionmentioning
confidence: 88%
“…For LSMO the magnetization, as a function of magnetic field, presents a hysteresis behavior for the NP while the bulk samples are free of magnetic losses . Xi et al concluded that it is due to the large surface anisotropy. Therefore, we assume that the magnetic anisotropy constant of the surface is larger than the bulk one, i.e.…”
Section: Model and Methodsmentioning
confidence: 99%